2004
DOI: 10.1007/s00198-004-1736-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hip quantitative computed tomography (QCT) measurements of bone mineral density and bone strength between glucocorticoid-treated and glucocorticoid-naïve postmenopausal women

Abstract: Chronic GC treatment in postmenopausal women resulted in significantly decreased BMD of the hip, measured by QCT, with loss of both trabecular and cortical bone. In addition, GC treatment decreased bone strength as determined by FEM. The reduced cortical and trabecular bone mass in the hip may contribute to the disproportionately high hip fracture rates observed in GC-treated subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…In particular, studies at the scale of 5-8 mm could be particularly useful for testing the idea that changes in bone microarchitecture and/or tissue material properties are responsible for any clinically relevant changes in bone biomechanical performance relative to density. For example, if it turns out that a particular treatment does not change bone quality at the scale of 5-8 mm, then attention can be focused on analysis of bone quality at higher physical scales, which should be feasible using current radiological techniques combined with finite element analysis [44,[60][61][62][63][64][65] or with whole bone mechanical testing. In this way a more complete picture of how characteristics of bone might explain discrepancies between aBMD and fracture incidence can be achieved.…”
Section: What Do We Know About Trabecular Bone Quality?mentioning
confidence: 99%
“…In particular, studies at the scale of 5-8 mm could be particularly useful for testing the idea that changes in bone microarchitecture and/or tissue material properties are responsible for any clinically relevant changes in bone biomechanical performance relative to density. For example, if it turns out that a particular treatment does not change bone quality at the scale of 5-8 mm, then attention can be focused on analysis of bone quality at higher physical scales, which should be feasible using current radiological techniques combined with finite element analysis [44,[60][61][62][63][64][65] or with whole bone mechanical testing. In this way a more complete picture of how characteristics of bone might explain discrepancies between aBMD and fracture incidence can be achieved.…”
Section: What Do We Know About Trabecular Bone Quality?mentioning
confidence: 99%
“…(8) FE modeling has been used in many osteoporosis biomechanics studies over the past 15 years (4)(5)(6)(9)(10)(11)(12) and most recently has been applied clinically to the assessment of glucocorticoid treatment at the hip. (13) In addition to providing noninvasive measures of strength and density, controlled parameter studies of the FE models of a patient's vertebra can be performed to assess the independent effects on vertebral strength of such parameters as bone geometry, average density, density distribution, and the relative contribution of the trabecular bone.…”
Section: Introductionmentioning
confidence: 99%
“…In general, with the calibration phantom employment, the precision error of QCT can be limited effectively. The QCT volumetric density assessment in the hip has also shown a very low (b2%) precision error [84,85]. All studies indicated that there was a significant association between the hip CTXA and DXA (rN0.95) with a high precision (CV b 2%) [13,20].…”
Section: Precision Of the Qct In Central Peripheral And Ctdx Assessmentmentioning
confidence: 99%
“…Those simulated strength models based on CT or MRI images included various bones (spine, hip, radius and tibia) validated by vitro studies [84,[142][143][144]. The two-or three-dimensional model map of finite element contained the pixel or voxel data of BMD or microarchitecture, and combined geometric behaviors that related to the orientation of loading force.…”
Section: Assessment Of Bone Mechanical Propertymentioning
confidence: 99%